MAQÄ€á¹¢ID AL-SYARÄªâ€™AH AL-SYÄ€á¹¬IBÄª DAN AKTUALISASINYA DALAM NILAI-NILAI FALSAFAH PANCASILA - Ahmad, Agustan (Hunafa: Jurnal Studia Islamika, 2011)
Allah swt. sent down the syarÄ«â€™ah to mankind with certain purpose. The Â Â purpose ofÂ  the syarÄ«â€™ah is to provide benefit to mankind and prevent them from things that are not good. However, the Muslim scholars (ulamÄâ€™) have different understanding on the purpose of the syarÄ«â€™ah and the procedures of its application. Therefore, the problem maqÄá¹£id al-syarÄ«â€™ah become the object of a separate study in Islamic law. One of the Muslim scholars (ulamÄâ€™) who specifically discusses this issue is al-SyÄá¹ibÄ« in his book, al-MuwafaqÄt. This article deals withÂ  maqÄá¹£id al-syarÄ«â€™ahÂ  of al-SyÄtibÄ« Â and its actualization in the philosophy valuesÂ  of Pancasila.